GERAKAN PRAMUKA SEBAGAI SARANA PENDIDIKAN KARAKTER DI MTS NW BENYER LOMBOK TIMUR - Hudaeni (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2023)
The purpose of this research is to identify the kinds of moral principles that may be cultivated through scout extracurriculars, the strategies for cultivating students' character education through scout extracurriculars, and the obstacles to character education in these contexts. The 45 participants are doing their research at MTs NW Benyer in East Lombok. This study is qualitative in nature, employing descriptive techniques such as interviews, observations, and written records. Data gathering, data presentation, data reduction, and data conclusions were all parts of an interactive data analysis process. The findings of this study suggest that participation in scouting extracurriculars can help shape nine distinct character traits, including a commitment to religious beliefs, discipline, care, environmental stewardship, tolerance, honesty, creativity, independence, and responsibility. Four scouting strategies are used to help shape kids' personalities through scout education: Both types of group systems (cooperating and competing) encourage students to be loyal and to be able to train themselves to be responsible people and to value more time in completing assignments; the three activities that are interesting and challenging encourage students to have a sense of curiosity so that they try to do some of each; and learning by doing makes it easier for students to gain knowledge so that they can quickly analyze a science because it is practiced directly.